2013
DOI: 10.1152/physiolgenomics.00135.2013
|View full text |Cite
|
Sign up to set email alerts
|

Usher proteins in inner ear structure and function

Abstract: Ahmed ZM, Frolenkov GI, Riazuddin S. Usher proteins in inner ear structure and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Subjects NRT-XHK-14 and NRT-XBU-39 (NRT ratio 1.00 and 0.94, respectively) were implanted because of long-term deafness based on Usher syndrome. Usher syndrome is a neurosensory, hereditary disorder affecting hearing, vision, and vestibular function in humans (22). Different genes encode proteins belonging to a family of transmembrane proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects NRT-XHK-14 and NRT-XBU-39 (NRT ratio 1.00 and 0.94, respectively) were implanted because of long-term deafness based on Usher syndrome. Usher syndrome is a neurosensory, hereditary disorder affecting hearing, vision, and vestibular function in humans (22). Different genes encode proteins belonging to a family of transmembrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Different genes encode proteins belonging to a family of transmembrane proteins. It is well known that false encoding leads to malfunction of the tip links of the stereocilia (23) and the rapid degeneration of inner hair cells (22,24). Dysfunction of the spiral ganglion, afferent neurons, and hair cell synapses is related to different proteins (25).…”
Section: Discussionmentioning
confidence: 99%
“…4 Based on the functional impairment of hair cells in Cib2 zebrafish morphants, it has been suggested that Cib2 is important for Ca 2+ homeostasis in sensory hair cells, and that loss of Cib2 function might affect processes like mechanotransduction, adaptation, electromotility and synaptic transmission. 4,24 Similarly, through functional studies in Drosophila, CIB2 was found to be essential for adequate phototransduction and maintenance of photoreceptor cells. 4 Furthermore, CIB2 has been demonstrated to be integrated into the Usher interactome via the association with whirlin and myosin VIIa.…”
Section: Introductionmentioning
confidence: 99%
“…The most common dual sensorineural disorder—Usher syndrome (USH)—is characterized by hearing loss and visual impairment. A spectrum of clinical severity exists and accordingly USH is classified into three types (USH1, USH2, and USH3) based on the degree of hearing loss, onset of retinitis pigmentosa (RP), and presence of vestibular dysfunction [Millan et al, ; Ahmed et al, ; Fettiplace and Kim, ]. Consistent with this phenotypic variability, 10 genes have been causally implicated in USH (http://hereditaryhearingloss.org/).…”
Section: Introductionmentioning
confidence: 99%